2021
DOI: 10.1016/j.bbih.2021.100325
|View full text |Cite
|
Sign up to set email alerts
|

The role of soluble epoxide hydrolase and its inhibitors in depression

Abstract: Evidence suggests that around 30 ​% of patients with depression do not respond to antidepressant treatment, with most of them having sub-chronic levels of inflammation. Soluble epoxide hydrolases (sEH) are enzymes present in all living organisms, which metabolize cytochrome P (CYP)-derived epoxy fatty acids to their corresponding diols. Accumulating evidence suggests that sEH plays a key role in the anti-inflammatory properties exerted by the metabolism of omega-3 polyunsaturated fatty acids (ω-3 PUFAs). Cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…Interestingly, ALOX15 expression was increased 24 h after LPS stimulation (1 µg/mL) in a murine microglial cell line in vitro; suggesting potential cell-type specific changes that may not have been picked up in our culture with only 10% microglial contribution [ 68 ]. sEphx2 expression was analyzed, as this enzyme is increased in depressive patients and brains of animal models of depression-like behavior, and its inhibition is a promising target for future treatment strategies of depression [ 69 ]. Additionally, it has been proposed that the sEphx2 enzyme could be involved in the metabolic inactivation of oxylipin mediators [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, ALOX15 expression was increased 24 h after LPS stimulation (1 µg/mL) in a murine microglial cell line in vitro; suggesting potential cell-type specific changes that may not have been picked up in our culture with only 10% microglial contribution [ 68 ]. sEphx2 expression was analyzed, as this enzyme is increased in depressive patients and brains of animal models of depression-like behavior, and its inhibition is a promising target for future treatment strategies of depression [ 69 ]. Additionally, it has been proposed that the sEphx2 enzyme could be involved in the metabolic inactivation of oxylipin mediators [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while not much is known about the functional significance of LXA5, it was shown to be involved in superoxide anion generation in canine neutrophil granulocytes [ 85 ], which may be also relevant for the brain during septic-like inflammation. More studies have already investigated the role of 18-HEPE, the precursor of resolvin E1, for its anti-inflammatory pro-resolving effects in peripheries such as the lung [ 62 , 86 ] and the brain [ 68 , 69 ]. For example, 18-HEPE has been demonstrated to induce brain-derived neurotrophic factor in Müller glia [ 87 ] or to inhibit TNFα secretion after LPS stimulation (0.5 µg/mL) in a murine macrophage cell line [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The causal relationship remains to be further assessed for n-3 deficiency and ADHD to support current data on correlations and conflicting results in clinical trials. Another novel treatment strategy involving the combined inhibition of n-3 fatty acids metabolism with n-3 fatty acids supplementation is presented by Borsini (2021) . This review summarized evidence, from both basic and clinical studies, supporting the use of soluble epoxide hydrolases (sHE) inhibitors (e.g., GSK2256294A and EC5026) in combination with other valid therapeutic approaches, in treating clinical depression.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, degradation of EETs by sEH abolishes their beneficial anti-inflammatory effects. Interestingly, it has been reported that sEH is overexpressed in neurological disorders such as depression [ 14 ], schizophrenia [ 15 ] and Parkinson’s disease (PD) [ 16 ], indicating the role of the enzyme in these neurodegenerative processes. Notably, it is widely described that sEH protein levels are increased in the brain of AD patients with Braak II/IV and several AD mouse models [ 17 ], including the senescence-accelerated mouse prone 8 (SAMP8) and 5XFAD mice.…”
Section: Introductionmentioning
confidence: 99%